2008
DOI: 10.1002/dev.20285
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to social and cognitive challenges in 8‐year olds with a history of prenatal cocaine exposure

Abstract: Cocaine-exposed infants have been found to have altered arousal responses but little is known about such responses in later childhood. Physiological responses to stressors were used to assess the arousal modulation of school-aged, cocaine-exposed children (n = 73) and two contrast groups, socioeconomically-matched controls (n = 58) and children with behavioral disturbance (n = 35). The behaviorally disturbed group had the highest heart rate across conditions but demonstrated a pattern of hyporesponsiveness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 69 publications
4
32
0
Order By: Relevance
“…Caregiver substance use [76,94] and maternal cocaine use during pregnancy [14,24,27,32,55,75,81,82,93] have been identified as risk factors for adverse child outcomes[45], and both risks are associated with certain environmental conditions known to alter child outcome, including poverty [35] and harsh parenting style [78]. These associations may confound the observed relations between prenatal cocaine exposure and teen cocaine use.…”
Section: Discussionmentioning
confidence: 99%
“…Caregiver substance use [76,94] and maternal cocaine use during pregnancy [14,24,27,32,55,75,81,82,93] have been identified as risk factors for adverse child outcomes[45], and both risks are associated with certain environmental conditions known to alter child outcome, including poverty [35] and harsh parenting style [78]. These associations may confound the observed relations between prenatal cocaine exposure and teen cocaine use.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prenatal exposures to nicotine [86], cocaine [87], and crystal methamphetamine [88] have been found to disrupt behavioral regulation. Interestingly, these have not been associated with the same degree of neurocognitive deficit as PAE [89].…”
Section: Interactions With Other Drugsmentioning
confidence: 98%
“…Sadly, this continued for many years, and the fears were fueled primarily by anecdotal reports and poorly designed studies. Subsequent research failed to replicate most adverse events or found them to be the result of other factors (eg, poor nutrition, inadequate prenatal care, maternal smoking, drinking, and other drug use) [3,4].…”
Section: Introductionmentioning
confidence: 99%